Casos y cosas peninsulares relacionadas con la denominada onomástica “vasco-aquitana” (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The article is devoted to several matters concerning the so-called Basque-Aquitanian Onomastics in the Iberian Peninsula. Some proposals are treated, reviewed and, when appropriated, new ones are offered mainly from the etymologic and morphological point of view not only in theonymy but also in personal onomastics and place-names. A useful instrument in the research has been the comparison of the material with onomastic elements properly Aquitanian and Iberian.
Keywords: Onomastics; Basque-Aquitanian; Iberian Peninsula; Revision; New Proposals